Constant Resistance and Yielding Support Technology for Large Deformations of Surrounding Rocks in the Minxian Tunnel - Jinyan Fan; Zhibiao Guo; Xiaobing Qiao; Zhigang Tao; Fengnian Wang (Advances in Civil Engineering)
During the excavation of the Minxian tunnel, problems of large deformations of surrounding rocks and failure of support structures appeared frequently, which caused serious influences on construction safety and costs of the tunnel. Based on laboratory analysis of mineral composition and field investigations on deformation characteristics of the surrounding rocks, the large deformation mechanism of surrounding rocks of the tunnel was considered as water-absorbing swelling molecules of carbonaceous slate and stress-induced asymmetric structural deformations of the surrounding rocks. The structural deformations of surrounding rocks mainly include bending deformation, interlayer sliding, and crushing failure of local rock blocks. Then, a new constant resistance and yielding support technology based on the constant resistance and large deformation (CRLD) anchor cable was proposed to control large deformations of surrounding rocks. The field tests and deformation monitoring were carried out. The monitoring results showed that compared with original support measure, the surrounding rock deformations, stresses of primary supports, and permanent lining using new support technology decreased greatly. Among them, the maximum deformation of surrounding rock was only 73 mm. The effects of field application and results of deformation monitoring showed that the new support technology can effectively control large deformations of the surrounding rocks in the Minxian tunnel.